By-Laws for the section on Archives and Human Rights - ICA Executive Board (2019)

Community-Based Transitional Justice Via the Creation and Consumption of Digitalized Storytelling Archives: A Case Study of Belfast’s Prisons Memory Archive - Anderson, Michelle (International Journal of Transitional Justice, 2019)
Other Publications

Oral History and Collective Memory: Documenting Refugee Voices and the Challenges of Archival Representation - Dudman, Paul (Atlanti, 2019)

Postcolonial Archives and the Question of Justice - Richards, Jill (The Cambridge Journal of Postcolonial Literary Inquiry, 2019)

Digital LGBTQ archives as sites of public memory and pedagogy - Van Haitsma, Pamela (Rhetoric and Public Affairs, 2019)
Other Publications

Trump’s agreements in Central America are dismantling the asylum system as we know it - Narea, Nicole (Vox, 2019)
The administration has started sending migrants back to Guatemala.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Guatemala Declares War on History - Lynch, Colum (Foreign Policy, 2019)
Looking for help on immigration, the Trump administration is silent in the face of Guatemala’s effort to seal its dirty war archive.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Terms of Reference: Open-Ended Working Group (OEWG) on the Examination of the Most Appropriate Legal Framework for the Memory of the World (MoW) Programme - Unesco; Memory of the World (Unesco, 2019)
Keywords: References - Boel et al. (2021); Archives and Human Rights

UNESCO Women in Africa History - Unesco (Unesco, 2019)
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Final Comprehensive Report - Truth & Dignity Commission (The Final Comprehensive Report, 2019)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Tunisia Truth Commission report (Part II): Justice and prisons, tools of oppression - Belhassine, Olfa (JusticeInfo.net, 2019)
Among the mechanisms on which the Bourguiba and Ben Ali regimes relied was the justice system which became a tool of government, and prisons, where all manner of violence and abuse took place. In its section on the mechanisms of systemic crimes, the report of the Truth and Dignity Commission (IVD) dissects these two tools […]
Keywords: References - Boel et al. (2021); Archives and Human Rights

Ahmed Timol: the quest for justice for people murdered in apartheid's jails - Thomas, Kylie (The Conversation, 2019)
In South Africa’s criminal justice system post-1994, the Timol case is the first to enact what can be properly understood as restorative justice.
Keywords: References - Boel et al. (2021); Archives and Human Rights

How South Africa can do better at reversing apartheid's legacies - Oosthuizen, Marius (The Conversation, 2019)
In matters of policy-making and governing, understanding the systemic complexity of interrelated forces is crucial to avoiding failure.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Guam World War II War Claims: A Legislative History - Guampedia.com (2019)
Keywords: References - Boel et al. (2021); Archives and Human Rights

A Paper Monument: The History of the Arolsen Archive - Borggräfe, Henning; Höschler, Christian; Panek, Isabel; Arolsen Archives (Bad Arolsen, 2019)
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Privacy Act in brief - Office of the Privacy Commissioner of Canada (priv.gc.ca, 2019)
Personal information, coverage, complaints
Last Modified: 2019-08-23
Keywords: References - Boel et al. (2021); Archives and Human Rights

Fury as Bolsonaro orders Brazil army to mark 55th anniversary of military coup - Phillips, Dom (The Guardian, 2019)
President’s instruction that defence ministry must hold ‘appropriate commemorations’ of 21-year military rule sparks outrage
Keywords: Americas; Brazil; Jair Bolsonaro; References - Boel et al. (2021); Archives and Human Rights; World news

The populist rewriting of Polish history is a warning to us all - Flieger, Estera (The Guardian, 2019)
Thirty years after communism ended, Poland’s past is again being manipulated for political motives, says Polish journalist Estera Flieger
Keywords: Europe; European Union; Poland; References - Boel et al. (2021); Archives and Human Rights; Second world war; World news

Managing cloud computing services in the United Nations system - Callejas, Jorge T. Flores; Dumitriu, Petru (United Nations, 2019)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Declaration of principles on freedom of expression and access to Information in Africa - Mute, Lawrence Muguru (African Commission on Human and Peoples’ Rights, 2019)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

145 spies - The Secret History of Fiat Brazil’s Internal Espionage Network and Collaboration With the Military Dictatorship - Cesar, Janaina; Grossi, Pedro; Cerantola, Alessia; February 24 2019, Leandro Demori (The Intercept, 2019)
The workers were a threat to the company’s bottom line, so Fiat Brazil suppressed labor organizing through an internal spy ring.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Jamal Khashoggi case: All the latest updates - Khashoggi, Jamal (aljazeera.com, 2019)
Here are the latest developments related to the Saudi journalist’s murder inside the kingdom’s consulate in Istanbul.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Adventures in archives: An interview with Trudy Huskamp Peterson - Maifeld, Stacey (Link Magazine, 2019)
Trudy Huskamp Peterson (’67 English, history), once the Acting Archivist of the United States, now travels the world rescuing records at risk.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Guiding Principles for Safe Havens for Archives at Risk - International Council on Archives (International Council on Archives, 2019)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

News from the ICA Section on Archives and Human Rights - 2019-12 (December) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Section on Archives and Human Rights - 2019-11 (November) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Section on Archives and Human Rights - 2019-10 (October) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-09 (September) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-08 (August) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-07 (July) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-06 (June) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-05 (May) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-04 (April) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-03 (March) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-02 (February) - Peterson, Trudy Huskamp (ICA, 2019)

News from the ICA Human Rights Working Group - 2019-01 (January) - Peterson, Trudy Huskamp (ICA, 2019)